Processing and properties of nanoporous hydroxyapatite ceramics - A. Raksujarit (2018)
Method for fabrication and properties of nanoporous hydroxyapatite (HA) ceramic were described in the present work. The nanoporous hydroxyapatite was derived from nano hydroxyapatite powder and polyvinyl alcohol (as a pore former). The HA nanopowder was obtained from vibro-milling for 4 h. The nanoporous ceramics were sintered at 1200 °C. Properties of the nanoporous ceramics were investigated using various methods. Average porosity of the final product was found to be 64.6 ± 1.4%. Open and interconnected pores were obtained with an average pore size less than 100 nm, confirming the nanoporous structure of this ceramic. A high bending strength of 14.7 ± 3.2 MPa for the nanoporous ceramic, shows significant promise as a potential bone repairing material. © 2009 Elsevier Ltd. All rights reserved.